Answer:
Step-by-step explanation:
Simplify .
Apply rule :
(1 + cot A + tan A) (sin A - cos A) = sin A tan A - cot A cos A
Answer:
see explanation
Step-by-step explanation:
Using the trigonometric identities
tan A = , cot A =
Consider the left side
(1 + cotA + tanA)(sinA - cosA)
each term in the second factor is multiplied by each term in the first factor.
1(sinA - cosA) + cotA(sinA - cosA) + tanA(sinA - cosA)
= sinA - cosA + cosA - + - sinA ( collect like terms )
= -
= ( sinA × ) - ( × cosA )
= sinAtanA - cotAcosA
= right side ⇒ proven
Answer:
yes
Step-by-step explanation:
x+6 = 1
x = -6 + 1
x = -5
Answer:
6
Step-by-step explanation:
5(3g + 2)/2 = 50 Multiply both sides by 2
5(3g + 2) = 50*2 = 100 Remove the brackets
15g + 10 = 100 Subtract 10 ***
15g+10-10 = 100 - 10 Collect like terms.
15g = 90 Divide by 15 ***
15g/15 = 90/15
g = 6
I don't know how to cut this down so that it requires only 2 steps. I guess that the two steps marked with *** are the 2 I would choose.
Answer:
g=6
Step-by-step explanation:
We can start by multiplying both sides by 2
5(3g+2)=100
Now we can distribute the 5 by using the distributive property
15g+10=100
Then we subtract 10 from both sides
15g=90
Divide both sides by 15
g=6
S = 10(1 - e^(kx))
Now when $325 is spent on advertising 2300 units are sold.
(a)Complete by solving for k. (Round your answer to 4 decimal places)
k = _______
(b) What number of units that will be sold if advertising is raised up to $425
_______ Units.